2006
DOI: 10.1088/0305-4470/39/21/s44
|View full text |Cite
|
Sign up to set email alerts
|

Casimir–Polder interaction between an atom and a cylinder with application to nanosystems

Abstract: Recently the Lifshitz theory of dispersion forces was extended for the case of an atom (molecule) interacting with a plane surface of a uniaxial crystal or with a long solid cylinder or cylindrical shell made of isotropic material or uniaxial crystal. The obtained results are applicable to nanosystems. In particular, we investigate the Casimir-Polder interaction between hydrogen atoms (molecules) and multi-wall carbon nanotubes. It is demonstrated that the hydrogen atoms located inside multiwall carbon nanotub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…For example, the multilayer graphite cylinder was considered as a simple model of a multiwalled carbon nanotube. Using this model, the Casimir-Polder interaction between hydrogen atoms (molecules) and multiwalled carbon nanotubes was investigated (Blagov et al, 2005;Klimchitskaya et al, 2006a). Later, Lifshitztype formulas have been obtained which describe the van der Waals and Casimir-Polder interaction between a graphene sheet and a material plate or a microparticle (Bordag et al, 2006) and a microparticle and a single-walled carbon nanotube (Blagov et al, 2007).…”
Section: Casimir-polder Interaction Of Atoms With Carbon Nanotubesmentioning
confidence: 99%
“…For example, the multilayer graphite cylinder was considered as a simple model of a multiwalled carbon nanotube. Using this model, the Casimir-Polder interaction between hydrogen atoms (molecules) and multiwalled carbon nanotubes was investigated (Blagov et al, 2005;Klimchitskaya et al, 2006a). Later, Lifshitztype formulas have been obtained which describe the van der Waals and Casimir-Polder interaction between a graphene sheet and a material plate or a microparticle (Bordag et al, 2006) and a microparticle and a single-walled carbon nanotube (Blagov et al, 2007).…”
Section: Casimir-polder Interaction Of Atoms With Carbon Nanotubesmentioning
confidence: 99%
“…Casimir-Polder forces at thermal equilibrium have been commonly investigated in the linear-response formalism [2][3][4]. Studies of a wide range of geometries such as semi-infinite half spaces [2][3][4][5], thin plates [6,7], planar cavities [8], spheres and cylinders [9] as well as cylindrical shells [5,6,10] have revealed that thermal CP forces are typically attractive in the absence of magnetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[196][197][198][199] Although reservations have been expressed about the reliability of this method for gap widths as small as the graphite interlayer distance, direct experience by this author shows that application of the Lifshitz theory to the interaction of multiwalled core and outer walls yields estimates of the retracting force in agreement with experimental data if the large uncertainty typical of such experiments at present is kept in proper consideration 301 (see Table 1 therein).…”
Section: Dispersion Force Accelerationmentioning
confidence: 80%
“…The above expression for U vdW, Lif includes neither the effect of finite thickness of the interacting slabs [196][197][198][199] nor of optical anisotropy. [200][201][202] For the moment, we shall assume that, from the standpoint of van der Waals energy computation, the nanotube geometry considered herein be equivalent to "wrapping" the standard parallel-plate system of the Lifshitz theory into two isotropic, concentric cylinders 137 with s/R OW , s/R core 1 ( Fig.…”
Section: B Lifshitz Theorymentioning
confidence: 99%
See 1 more Smart Citation